Fatores associados ao diagnóstico de tuberculose pulmonar entre suspeitos da doença na rotina de unidades de saúde de Fortaleza, CE - Alcântara, Cid Carlos Soares de (2010)
Tuberculosis (TB) is a disease that has challenged mankind since antiquity. It was believed that with the new technology, infectious diseases would be easily tracked and banned. The reality has been presented differently, despite advances in knowledge of tuberculosis and technology available for its control, the current picture is far from the targets set by governments. It is essential to the study of factors associated with pulmonary tuberculosis, since they are present in the prime-infeccção in relapse and multi-drug resistant pulmonary TB. Knowledge of data related to TB in the general population and specific groups at risk for TB are crucial to assess the epidemiological reality of our environment allowing proper organization of prevention and care activities. OBJECTIVE: To investigate factors associated with the diagnosis of TB, the frequency and characteristics of pulmonary tuberculosis with respiratory symptoms in three routine health services in Fortaleza. Cross-sectional study of quantitative accomplished through the application of a questionnaire in patients from three health units of Fortaleza. Respondents were divided on outcome of patients with tuberculosis and non tuberculosis outcome. We studied the influence of sociodemographic factors, housing conditions, behavioral factors, antecedents related to TB infection and clinical outcome for tuberculosis. RESULTS: The rate of pulmonary TB patients with respiratory symptoms among the study sample was 41.2%, but this data can not be extrapolated, the socio demographic and clinical outcome independently associated with TB were cough, fever and weight loss considering the level of six percent of significance. The main method used to assist diagnosis of TB in patients suspected of units studied in Fortaleza was the chest radiograph. The susceptibility profile of Mycobacterium tuberculosis showed 8.82 percent of MDR strains and sensitivity to isoniazid, rifampin, ethambutol and streptomycin from 88.23 percent in the samples taken and can not be extrapolated. If all TSA excluded from the hospital and found only Messejana TSA health posts, the resistance value reduces to a case of MDR 28 to TSA made, representing 3.6% of the sample, most patients with pulmonary TB had AFB positive only a cross, which may mean duration of disease not so long.